EFFECT OF MOTIVATIONAL FACTORS ON DECISION OF SECONDARY SCHOOL TEACHERS TO OPT TEACHING AS A PROFESSION - Sumaira Rashid (European Scientific Journal, ESJ, 2014)
The present study intends to explore the effect of most significant factors on secondary school teachers to choose teaching as ultimate profession. Sample of the study comprises of 288 secondary school teachers from Govt Secondary girls schools of Pakistan. The results showed the difference of teachers perceptions regarding age, education, qualification, annual income and experience. The findings explored only difference of opinion towards experience regarding teachers desires of becoming teacher . The most influential factor that opted by the teachers was salary. The participants showed little satisfaction towards country pay scales and salary packages.